IN VITRO CELLULAR RESPONSE TO INTERFERON-α2 IN CHILDREN WITH INFECTIOUS MONONUCLEOSIS CAUSED BY EPSTEIN-BARR VIRUS - L. M. Kurtasova; N. A. Shakina; A. R. Schmidt (Медицинская иммунология, 2016)
Our objective was to study in vitro response of blood leukocytes to IFNα2 in children with infectious mononucleosis, caused by the Epstein-Barr virus, during the acute phase of disease. Patients and methods. Sixty-five children at the age of 4 to 6 years, being in acute phase of infectious mononucleosis caused by the Epstein-Barr virus (EBV) were under study. The control group consisted of 36 healthy children. In vitro response of blood leukocytes to IFNα2 was determined by the original technique (L.M. Kurtasova et al., 2007). Chemiluminescence of the blood leukocytes was studied according to De Sole et al. (1989). Results. We observed that clinical condition of the children with EBV infection in acute phase of the disease was characterized by decreased ranges of blood leukocyte response to IFNα2, and dependence of the cellular response on the dose, as well as severity of the disease. In conclusion, these data suggest a need for individual strategy of interferon therapy for the children with infectious mononucleosis caused by the Epstein-Barr virus.